Macronutrientes (N, P, K), pH y CE en el horizonte B de los perfiles de suelo en el campus “La María”, del cantón Mocache - Quintana Franco, Mildred Yuliana (2019)
The research project was carried out on the grounds of the State Technical University of Quevedo of the Campus "La María", located at kilometer 7 1/2 of the Quevedo-El Empalme road in the province of Los Ríos. The main objective of this study is to determine macronutrients (N, P, and K), pH and CE on horizon B, to know their status and conditions of each area established with agricultural plantations for agricultural use. Specific objectives were: Analyze the content of nitrogen (N), phosphorus (P) and potassium (K). Determine the pH and electrical conductivity content of the soil profiles corresponding to horizon B. This test considered 2 stages, the first with a duration of 3 months, between preparation and collection of samples and the second stage corresponds to the laboratory in which chemical analysis determination methodologies were performed on the different variables. A Completely Random Design (DCA) was used with 20 treatments and three repetitions. The results were analyzed in the InfoStat statistical program and tested at 95% probability. The average NH4+ 14.19 ppm by scale is considered as a low percentage in nitrogen content just as the phosphorus content was 3.57; In addition, the potassium concentration in the different soils has an average of 315.9 ppm. The pH content (H2O and CaCl2) averaged 7.18 and 6.14 corresponding to the neutral and slightly alkaline classification. While in electrical conductivity obtained 34.39 s/cm on horizon B of the Campus "La María" being this range a low value in salinity concentration therefore it is necessary and of paramount importance not to salinize the soils and perform reasoned fertilization. On the other hand according to the groups of grass, perennial and annual crops in the areas of agricultural use where they are established reflect optimal conditions for the growth, development and productivity of them. Keywords: Preparation, Soil, Concentration, Plantations, Collection